Cyber Insurance in Malaysian Organisations: An Introductory Journey - Raju, Rajeswari; Rahman, Nur Hidayah Abdul; Sangaran, Sritharan; Yasin, Sharifah Nurulhikmah Syed; Eri, Zeti Darleena (International Journal of Social Science Research, 2024)
Over the past century, many profound technological, economic, and social transformations have occurred. 21st century emerged as of technology and the borderless world; businesses have embraced more strategic ways to handle risk in computing; Cyber Risk Management (CRM) has become one of the essential components in risk management initiatives that seek to mitigate and analyse the multitude of new risks. One risk mitigation process is investing in cyber insurance to safeguard IT assets from cyber threats by transferring such risks to another party known as the insurer. However, implementing cyber insurance in Malaysia is still a considerable organisationsal gap. Unlike any other insurance purchased by default due to financial obligations, many organisations in Malaysia are still lackadaisical towards cyber insurance. The research looks into the factor that contributes to the gap. The study starts with identifying the research background and problem statement and then collecting the data. 30 semi-structured interviews were conducted. The data was collected from 30 experienced Malaysian organizations in the public and private sectors. Finally, the outcome is analysed and concluded.